ENGLISH AND BIELORUSSIAN METAPHORS IN ECONOMIC DISCOURSE - Kukharenka, N.S. (Studia Philologica, 2015)
The purpose of this article is to examine the features of metaphor in economic discourse. Economy-related lexical units as well as structures typical for economic discourse have been actively utilized in individual and group communication. The article discusses samples of economic discourse selected from two British periodicals, the Financial Times and the Economist, and two Bielarusian ones, Звязда and Народная Воля.